Sodium‐glucose co‐transporter 2 inhibitors and the risk of fractures: A propensity score‐matched cohort study. Issue 12 (24th October 2019) - Adimadhyam, Sruthi; Lee, Todd A.; Calip, Gregory S.; Smith Marsh, Daphne E.; Layden, Brian T.; Schumock, Glen T.
Abstract: Purpose: To determine the risk of fractures associated with sodium‐glucose co‐transporter 2 inhibitors (SGLT2i) compared with dipeptidyl peptidase‐4 inhibitors (DPP4i). Methods: We conducted a retrospective cohort study using data from the Truven Health MarketScan (2009‐2015) databases. Our cohort included patients newly initiating treatment with SGLT2i or DPP‐4i between 1 April 2013 and 31 March 2015 that were matched 1:1 using high dimensional propensity scores. Patients were followed up in an as‐treated approach starting from initiation of treatment until the earliest of any fracture, treatment discontinuation, disenrollment, or end of data (31 December 2015). Risk of fractures was determined at any time during the follow‐up, early in therapy (1‐14 days of the follow‐up), and later in therapy (15 days and beyond). Cox proportional hazards models were used to determine hazard ratios and robust 95% confidence intervals (95% CI). Results: After matching, our cohort included 30 549 patients in each treatment group. Over a median follow‐up of 219 days, there were 745 fractures overall. The most common site for fractures was the foot (32.7%). The effect estimates for fracture risk occurring at any time during follow‐up, early in therapy, and later in therapy were HR 1.11 [95% CI 0.96‐1.28], HR 1.82 [95% CI 0.99‐3.32], and HR 1.07 [95% CI 0.92‐1.24], respectively. Conclusion: There is a possible increase in risk for fractures early in therapy with SGLT2i. Beyond this initial period, SGLT2is had no apparent effect on the incidence of fractures.